Management of solid healthcare wastes in some government healthcare facilities in Enugu state, Southeast Nigeria: a cross-sectional study - Umegbolu, Emmanuel I.; Ozoejike, Innocentia N. (International Journal Of Community Medicine And Public Health, 2017)
Background: The significance of healthcare wastes (HCWs) consists in their hazardous component, which constitutes real danger to public health. In Nigeria, healthcare waste management (HCWM) has remained a problem yet to be properly recognized and so addressed. The study aimed to sensitise health workers and the public on the need for proper management of HCWs, considering the public health implications of not doing so. Methods: The waste management systems of ten healthcare facilities (HCFs) were assessed, using a modification of the WHO rapid assessment tool. In each HCF, segregated wastes were collected daily for ten days and quantified by weighing, using a spring balance. Results: Administratively, the HCWM system was poor in the ten HCFs (40.6%). 70% of them had satisfactory waste segregation, 81%, good waste treatment, and 26.7% adequate transportation methods for waste. None of the HCFs had budget allocation for HCWM, and 90% had inadequate storage facilities. Mean waste generation was 1.81 kg/day, 0.23 kg/patient/day, 0.16 kg/bed/day, and proportion of infectious wastes 16.8%. Correlation between the number of patients and proportion of infectious waste, was positive, strong and significant (r=0.80, p=0.01), and between bed occupancy rate and proportion of infectious waste, was positive too, but weak, and insignificant (r=0.34, p=0.34). Conclusions: In view of the identified weaknesses of the ten HCFs in HCWM, budget allocations for HCWM, improving waste storage facilities and transportation, with strengthening of waste segregation, collection, and treatment, would help to ensure adequate HCWM in the HCFs.